Learning for sustainable development through innovation in SMEs - Hamburg, Ileana (Advances in Social Sciences Research Journal, 2020)
The aim of this article is to investigate different types of innovation companies can develop, the relationship innovation and learning/training, defined as sustainable factors in small and medium sized enterprises (SMEs). An innovative learning program for SME employees is described, which was developed and tested within a European project. The findings, also as a consequence of the learning program offered to SMEs, prove that SMEs can develop and use innovative training/learning to achieve suitable competences to improve the impact on sustainability in their organizations.